THE ROLE OF THE PRINCIPAL IN DEVELOPING A RELIGIOUS CULTURE AT SMPN 4 BOYOLALI - Meti Fatimah; Muh Nur Rochim Maksum; Deddy Ramdhani (Profetika: Jurnal Studi Islam, 2021)
This study aims to determine the importance of the role of the principal in developing a religious culture in schools. This study uses a qualitative approach aimed at describing and analyzing natural phenomena, events, social activities regarding the development of religious culture through the internalization of moral and religious values at SMPN 4 Boyolali. Documentation, observation and interviews are the methods used to collect data. Meanwhile, the technique of analyzing and analyzing the data is using data reduction, categorizing the checking of the validity of the data and interpreting the data. The results of this study indicate that developing a religious culture in schools requires systematic policies and concepts.